2023
DOI: 10.7150/ijbs.81824
|View full text |Cite
|
Sign up to set email alerts
|

Berberine inhibits high fat diet-associated colorectal cancer through modulation of the gut microbiota-mediated lysophosphatidylcholine

Abstract: Dietary fat intake is positively associated with elevated risk of colorectal cancer (CRC). Currently, clinical treatments remian inadequate bacause of the complex pathogenesis of CRC induced by a high-fat diet (HFD). Mechanistically, imbalances in gut microbiota are associated with HFD-associated colorectal tumourigenesis. Therefore, we investigated the anti-tumor activity of berberine (BBR) in modulating the dysregulated gut microbiota and related metabolites by preforming 16S rDNA sequencing and liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Previous studies have suggested that both the quality and quantity of dietary fat intake might influence the composition and abundance of gut microbiota. 74 The unsaturated fatty acids change the composition and abundance of gut microbiota by enhancing ratio of Bacteroidetes to Firmicutes 75 . N -3 polyunsaturated fatty acids ( N -3 PUFA) can result in beneficial alterations in gut microbiota, including the addition of Bifidobacterium , Lactobacillus , Streptococcus , Vibrio desulphuricum , and Akkermania mucophilus .…”
Section: Influences Of Different Dietary Nutrients On Osteoporosis By...mentioning
confidence: 99%
“…Previous studies have suggested that both the quality and quantity of dietary fat intake might influence the composition and abundance of gut microbiota. 74 The unsaturated fatty acids change the composition and abundance of gut microbiota by enhancing ratio of Bacteroidetes to Firmicutes 75 . N -3 polyunsaturated fatty acids ( N -3 PUFA) can result in beneficial alterations in gut microbiota, including the addition of Bifidobacterium , Lactobacillus , Streptococcus , Vibrio desulphuricum , and Akkermania mucophilus .…”
Section: Influences Of Different Dietary Nutrients On Osteoporosis By...mentioning
confidence: 99%
“…For instance, metabolic dysfunction induced by an HFD is associated with alterations in gut microbial composition and metabolic products [19,33]. Berberine has been shown to effectively alleviate gut dysbiosis in mice fed an HFD; to increase the abundance of beneficial microorganisms such as Akkermansia and Parabacteroides; and to directly inhibit HFD-associated colorectal cancer through gut microbiota-regulated lyso-phosphatidylcholine [34]. A spirulina platensis polysaccharides intervention has been found to alter the relative abundance of intestinal microorganisms and decrease cecal levels of propionic acid in HFD-fed rats, thereby attenuating lipid and carbohydrate metabolism disorders induced by the HFD [22,35].…”
Section: Dietary Transition Reshapes the Gut Microbiota Of Silkwormsmentioning
confidence: 99%
“…Berberine intake has been shown to alleviate gut barrier disruption and inhibit colon inflammation in high-fat-diet-fed mice. Meanwhile, berberine can ameliorate gut microbial dysbiosis and can induce increases in beneficial gut microbiota, including Akkermansia and Parabacteroides [7].…”
Section: Effects Of Dietary Habits On the Gut Microbiotamentioning
confidence: 99%